2000
DOI: 10.2105/ajph.90.6.940
|View full text |Cite
|
Sign up to set email alerts
|

Helping women quit smoking: results of a community intervention program

Abstract: OBJECTIVES: This intervention was implemented to reduce the prevalence of cigarette smoking among women. METHODS: We used community organization approaches to create coalitions and task forces to develop and implement a multicomponent intervention in 2 counties in Vermont and New Hampshire, with a special focus on providing support to help women quit smoking. Evaluation was by pre-intervention and post-intervention random-digit-dialed telephone surveys in the intervention counties and the 2 matched comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, as much as many of these disadvantages concern behaviors, behavioral approaches stressing social modeling, coaching on specific approaches to adopting healthy behaviors, and so on are central to many public health– and community–based efforts to address these burdens. 100, 176–183 Indeed, counter to expectations that low-income or otherwise disadvantaged groups may be “poor bets” to respond to health promotion interventions, behavioral interventions focused on smoking 184186 or type 2 diabetes 187 have been especially effective amidst high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, as much as many of these disadvantages concern behaviors, behavioral approaches stressing social modeling, coaching on specific approaches to adopting healthy behaviors, and so on are central to many public health– and community–based efforts to address these burdens. 100, 176–183 Indeed, counter to expectations that low-income or otherwise disadvantaged groups may be “poor bets” to respond to health promotion interventions, behavioral interventions focused on smoking 184186 or type 2 diabetes 187 have been especially effective amidst high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based research has found that peer-to-peer transmission of tobacco harms is an effective strategy in reducing use because peers are less intimidating than physicians ( Secker-Walker et al, 2000 ; Williams et al, 2011 ). Most participants reported that they shared information from the presentations with others, although women in the RHP condition were not more likely to share than women in the GHP condition, contrary to predictions (see Figure S6 and Table 2 , Share presentation model).…”
Section: Discussionmentioning
confidence: 99%
“…Studies confirm that women rely heavily on social learning to navigate the avoidance of toxic foods and substances that can disrupt fetal development during pregnancy ( Henrich & Henrich, 2010 ; Placek, Madhivanan, & Hagen, 2017 ). In addition, peer-to-peer transmission of tobacco harms is an effective strategy in reducing use because peers are less intimidating than physicians ( Secker-Walker et al, 2000 ; Williams et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Culturally targeted interventions have shown improvement in smoking among high risk women. 66 , 67 The CDC recently published recommendations for community-based programs to reduce obesity, many of which also can be implemented at the state level or nationally. These include (1) increasing the availability and affordability of healthy foods and beverages, promoting healthy portion size, and decreasing the availability and affordability of unhealthy foods in public community settings such as schools; (2) increasing the number of supermarkets in underserved areas; (3) incentivizing local food provid-ers to offer healthier food and beverage choices in underserved areas; (4) improving food distribution from local farms via farmers′ markets and other community-based initiatives; (5) limiting advertising of unhealthy foods and beverages; (6) discouraging consumption of sugar-sweetened beverages; (7) supporting breastfeeding; (8) improving physical education in schools and increasing opportunities for afterschool sports; (9) improving the built environment to create safe spaces for recreation including sports, biking, and walking; and (10) creating community partnerships with groups such as faith-based organizations, youth organizations, and industries to combat obesity.…”
Section: Discussion: Road Map To Improve Women's Healthmentioning
confidence: 99%